Andean ontologies : new archaeological perspectives - Lozada, María Cecilia; Tantaleán, Henry, 1974- (University Press of Florida, 2019)
This volume explores the Pre-Columbian Andean concepts of time, space, and the human body through objects, skeletal remains, and language. This interdisciplinary approach to conceptualizing what the Andean concepts of being may have been brings contemporary approaches to past notions of the sacred, with each discipline adding its own unique perspective to the Andean ontology. A particular strength of this volume is that most of the contributors are South American researchers, offering North American scholars entry into scholarship that has been confined to Spanish language publications.